10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
Women with HIV experience high rates of trauma, chronic stress, and depression, which are linked to cognitive impairment. Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, glucocorticoid receptor function, inflammation, and HIV persistence are candidate mechanisms, yet no interventions directly target these pathways. To determine whether low-dose hydrocortisone (LDH), a pharmacologic modulator of HPA axis function, improves cognition in women with HIV and to examine neuroendocrine, immune, and HIV-related mechanisms underlying treatment effects. This 2-phase, placebo-controlled randomized clinical trial was conducted at Johns Hopkins University between November 2017 and July 2023. Participants were randomized to 1 of 4 treatment sequences: Phase 1 was a double-blind, placebo-controlled crossover trial testing the immediate (30 minutes) and delayed (4 hours) cognitive effects of a single LDH dose. Phase 2 was a double-blind, placebo-controlled, 4-week trial of the effects of daily LDH compared with placebo on cognition and safety parameters. Participants were virally suppressed women aged 18 to 65 years with HIV and elevated self-reported stress, mood or anxiety disorder, or both and objective impairment in at least 1 cognitive domain. Single-dose LDH (10 mg orally; phase 1) or daily LDH (10 mg orally; phase 2) compared with placebo. The primary outcomes were verbal learning and memory (assessed with the Hopkins Verbal Learning Test-Revised), working memory (assessed with the Letter-Number Sequencing task), and visuospatial abilities (assessed with the Repeatable Battery for the Assessment of Neuropsychological Status Line Orientation subtest). Secondary outcomes included additional cognitive domains (eg, attention and executive function), safety metrics, and mechanistic markers (eg, salivary cortisol, inflammatory biomarkers, glucocorticoid receptor function, and HIV reservoirs). Eighty-one women (mean [SD] age, 55.2 [8.0] years) were randomized. LDH produced a cortisol increase peaking 75 minutes post dose (Cohen d = 1.30; 95% CI, 1.00 to 1.60; P < .001). At 4 hours post dose, LDH significantly improved learning compared with placebo (Cohen d = 0.35; 95% CI, 0.02 to 0.69; P = .03), whereas the improvement in verbal delayed recall was not significant (Cohen d = 0.33; 95% CI, -0.01 to 0.67; P = .05). LDH improved attention at the 30-minute (Cohen d = 0.38; 95% CI, 0.04 to 0.71; P = .02) and 4-hour (Cohen d = 0.42; 95% CI, 0.08 to 0.76; P = .01) time points. LDH had no effect on working memory or visuospatial abilities. In phase 2, daily LDH, but not placebo, improved memory (Cohen d = 0.71; 95% CI, 0.22 to 1.20; P = .005), although the treatment × time interaction was not significant (Cohen d = 0.42; 95% CI, -0.25 to 1.08; P = .22). LDH was well tolerated. No associations were observed between LDH-related biomarkers and cognitive changes. In this randomized clinical trial, LDH produced acute and short-term improvements in verbal learning, memory, and attention in virally suppressed women with HIV. These findings suggest that HPA axis modulation may represent a therapeutic pathway for cognitive dysfunction in HIV. Peripheral biomarkers did not account for these cognitive benefits, suggesting that other biological mechanisms may underlie LDH's effects. ClinicalTrials.gov Identifier: NCT03237689.